Pengaruh Kualitas Pelayanan BEI Yogyakarta yang Dimoderasi Program SPM Terhadap Keputusan Investasi Kaum Millenial The Influence of BEI Yogyakarta's Service Quality Which is Moderated By The SPM Program on Investment Decisions Of Millennials - Sintya Dewi, Made Ayu; Triana, Dewi (EBBANK, 2023)
This research aims to analyze the Yogyakarta BEI Service Quality Dimensions Moderated by the SPM Program on Investment Decisions of Millennials. The research data used comes from the community, especially Yogyakarta millennials who have participated in the SPM program organized by BEI Yogyakarta and have opened an account. By using the method of distributing questionnaires to respondents via Google Form. The number of respondents based on participant data was 120 people. The data processing method uses multiple regression analysis with additional analytical methods of validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, MRA regression test, and t test. The results of this research partially show that the five dimensional variables of service quality (tangibles, reliability, responsiveness, assurance and empathy) have a significant influence on investment decisions of millennials, while the test results of the SPM program as a moderating variable on the five variables on investment decisions of millennials contain 3 variables. The independent variables that have a significant influence are tangibles, reliability and assurance, while the other 2 variables (responsiveness and empathy) have no significant influence.